Achieving atomistic control in materials processing by plasma–surface interactions. (6th June 2017) - Chang, Jeffrey; Chang, Jane P
Abstract: The continuous down-scaling of electronic devices and the introduction of functionally improved novel materials require a greater atomic level controllability in the synthesis and patterning of thin film materials, especially with regards to deposition uniformity and conformality as well as etching selectivity and anisotropy. The richness of plasma chemistry and the corresponding plasma–surface interactions provide the much needed processing flexibility and efficacy. To achieve the integration of the novel materials into devices, plasma-enhanced atomic layer processing techniques are emerging as the enabling factors to obtain atomic scale control of complex materials and nanostructures. This review focuses on an overview of the role of respective plasma species involved in plasma–surface interactions, addressing their respective and synergistic effects, which is followed by two distinct applications: plasma-enhanced atomic layer deposition (ALD) and atomic layer etching (ALE). For plasma-enhanced ALD, this review emphasizes the use of plasma chemistry to enable alternative pathways to synthesize complex materials at low temperatures and the challenges associated with deposition conformality. For plasma enabled ALE processes, the review focuses on the surface-specific chemical reactions needed to achieve desirable selectivity and anisotropy.